Room temperature water infusion during colonoscopy insertion induces rectosigmoid colon mucus production - El Rahyel, Ahmed; McWhinney, Connor D.; Parsa, Nasim; Lahr, Rachel E.; Vemulapalli, Krishna C.; Rex, Douglas K. (Endoscopy, 2020)
Background Water filling during colonoscopy improves several colonoscopy outcomes. We evaluated an anecdotal observation that room temperature water filling during colonoscope insertion results in mucus production in the left colon, which may impair mucosal visualization during withdrawal.Methods We performed 55 colonoscopies with either water or saline filling during insertion, and video recorded the examinations. Three blinded observers scored the amount of mucus visible on the video recordings.Results 29 patients had water filling and 26 patients had saline filling during insertion. Demographic features, procedure indications, volume of infused fluid, and insertion time to the cecum were similar in the two groups. All three blinded observers rated the mucus as greater after water filling than after saline (median 3 out of 5 vs. 1 out of 5; P < 0.001), with a kappa value for interobserver agreement of 0.364 (P < 0.001).Conclusion Room temperature water filling is associated with mucus production by the rectosigmoid colon, requiring additional cleansing during withdrawal.